Penerapan Model The Power of Two Berbantuan Media Diorama untuk Meningkatkan Hasil Belajar Peserta Didik di Kelas V SDN 12 Tanah Sirah - Kartila Primalti; Yanti Fitria; Zuryanty; Yeni Erita (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The low learning outcomes of fifth-grade students in science at SDN 12 Tanah Sirah, Padang City, are caused by teacher-centered learning, low student involvement, and the use of less interesting media. This study aims to improve science learning outcomes through the application of *The Power of Two* model assisted by diorama media. The study used Classroom Action Research (CAR) with qualitative and quantitative approaches implemented in two cycles, including planning, implementation, observation, and reflection. The research subjects consisted of one teacher and 20 fifth-grade students. Data were collected through tests and non-tests in the form of observation sheets and analyzed descriptively qualitatively and quantitatively using percentages and average values. The results showed that the application of *The Power of Two* model assisted by diorama media improved the quality of learning implementation, teacher activities, and student activity in each cycle. This improvement had an impact on student learning outcomes, which increased from an average value of 73.42 to 90.36, with learning completion reaching 100% in cycle II. Thus, the *The Power of Two* model assisted by diorama media is effective in improving elementary school students' science learning outcomes.